Cultural Identity, Kinship Systems, Traditional Practices and Beliefs in Savu Raijua’s Folklores: A Thematic Analysis - Tlonaen, Zuvyati Aryani; Ludji, Ifoni; Tamelan, Thersia Magdalena; Hambandima, Erny S.N (Jurnal Antropologi: Isu-Isu Sosial Budaya, 2025)
This study explores the unique folklore of Sabu Raijua enriching cultural enthusiasts and providing valuable insights for academics and students in folklore, anthropology, and cultural studies. The intricate relationship between folklore and the broader cultural and social context of the Sabu Raijua community within the folklore can be analyzed to provide a deeper understanding of its significance. To obtain the data, two folklores was analysed using thematic analysis to identify patterns and themes from collected data. Literary research was explored to validate the findings, ensuring the results were relevant. The methodology involved a detailed process of repeatedly reading the story, coding, and grouping data into themes followed by validating and narrative interpretation. The two stories highlight the cultural values of the Sabu Raijua people through genealogy, naming system, geographical identity, and supernatural powers. They reflect social values such as family responsibilities while also showcasing key rituals like Happo Ana. This study offers insight into Sabu culture, emphasizing its traditions and the central role of magic and mythology in daily life.